Pregnant women's participation in support groups in Enugu state, Nigeria (2015-2016): experiences and influences on their intentions to deliver in a health facility - George, Eki Osarenoma (My University, 2017)
Introduction Proper access to antenatal care services and skilled birth attendants during delivery is key to reducing maternal deaths. But studies show that women in rural communities in Nigeria, do not access Ante-Natal Care (ANC) and a lower proportion deliver in a health facility. An internationally funded maternal and child health program in Enugu State, Nigeria introduced the concept of using the support group to improve uptake of antenatal care services and health facility delivery services. The support group comprised of pregnant women who encouraged and supported each other from pregnancy through to delivery in a health facility. However there was no documented evidence to show that the support groups actually influenced women’s intention to deliver in a health facility. This research work is being carried out to address this gap – by providing evidence on whether the support groups influenced women’s intention to deliver in a health facility. Methods Following informed consent, a qualitative study was conducted. Data was collected from women aged between 18 years and 49 years who were in a support group in seven health facilities in Nkanu West Local Government Area (LGA) of Enugu State, Nigeria. Seven Focus Group Discussions (FGD) and In-depth Interviews (IDI) were conducted. The data analysis was done using NVIVO software. All field notes were checked against translated interviews to ensure completeness and correctness. Inter-coding agreement, triangulation of data was done to ensure consistency. A descriptive analysis of the findings against theoretical framework was done and all findings also linked to objectives of the study. ii Results The pregnant women support group is shown to influence pregnant women’s intention to deliver in a health facility. Reasons for joining the group included; increasing knowledge about pregnancy and the benefits of ANC attendance and health facility delivery, socio-economic and spiritual support. However, the intention to deliver in a health facility is influenced by other factors such as; good and caring attitude of health workers, availability of qualified health workers, and better health infrastructure to respond to complications and emergencies. Other influences such as mother-in-law and spouses were also identified. The members of the group enjoyed benefits such as; visitation and presentation of gifts by support group members upon delivery, post- natal care and sometimes financial support. Despite these benefits, the goal of having a safe delivery remained the ultimate benefit of being a member of the support group. The existence, management and survival of the group other than by its members were dependent on the health facility workers. Conclusion The study demonstrated that the support group intervention did influence pregnant women’s intention to deliver in a health facility. But, the intention to deliver in a health facility was also driven by other factors such as; availability of skilled health workers, improved infrastructure and the cost of health services.
A research report submitted to the Faculty of Health Sciences (School of Public Health), The University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Public Health in the field of Social Behaviour Change and Communication. June , 2017
Keywords: Pregnant Women Self-Help Groups